Rasmus Paludan, Burning of the Qur’an and Swedish Media: A Critical Discourse Analysis - Larsson, Göran; Mattsson, Christer (Temenos - Nordic Journal for the Study of Religion, 2024)
This article scrutinizes the public debate in Sweden that followed the heated riots that took place when Rasmus Paludan burned the Qur’an in the spring of 2022. The Easter holiday in 2022, which coincided with Ramadan, served as the backdrop for the Danish-Swedish provocateur Rasmus Paludan. Our study is based on a critical discourse analysis (CDA) of 60 public opinion pieces published between 24 and 30 April 2022, one week after the so-called Easter riots. The Swedish media at this time featured many different responses to the burning of the Qur’an, as well as strong public opinions about how the riots were dealt with, and why the riots erupted in the first place. We argue that the discussion that followed Paludan’s public rallies in Sweden unfolds a dilemma between freedom of speech on the one hand and freedom of religion on the other. By deploying critical discourse analysis, this study helps us observe the discursive orders that regulated the debate and identify recurring topics and tropes in public media. The overall results indicate that the riots are mainly viewed as the result of a failed multicultural policy in which Islam is discussed as an obstacle to liberal democracy and thus freedom of speech. Material reasons – poverty, unemployment, and racism – are largely omitted from the debate.